The effects of vacuum and freeze-drying on the physicochemical properties and in vitro digestibility of phenolics in oyster mushroom (Pleurotus ostreatus) - Ucar, Tutku Merve; Karadag, Ayse (SPRINGER, 2019)
The oyster mushroom (Pleurotus ostreatus) was dehydrated by vacuum and freeze drier, and their proximate composition, physical properties (change in color and size, rehydration), phenolic compounds and antioxidant activities were compared. The bioaccessibility of phenolics and antioxidant activity were determined by using an in vitro digestion model coupled with a simulated intestinal barrier. The extraction yield, total phenol content, antioxidant activity and the number of individual phenolics were higher in vacuum dried mushrooms. Gallic acid, protocatechuic acid, p-hydroxybenzoic acid, p-coumaric acid, and o-coumaric acid were phenolic acids found in the extracts of oyster mushrooms. The different physical structures of food matrix attained by drying would influence the digestibility of bioactive compounds, a great portion of phenolics remained in the gut, and bioaccessibility index of mushroom phenolics identified in this study was between 17.8 and 41.9%. Regarding the color, size reduction, and rehydration properties, freeze drying was a preferable method for oyster mushroom preservation. However, vacuum drying was a better alternative in terms of extractability of phenolics from mushroom powders and their fate during in vitro gastrointestinal digestion.
Keywords: Oyster mushroom; Phenolics; Drying; Bioaccessibility; In vitro gastrointestinal digestion; ANTIOXIDANT PROPERTIES; GASTROINTESTINAL DIGESTION; AGARICUS-BISPORUS; POLYPHENOLS; QUALITY; POLYSACCHARIDES; CAPACITIES; COPRODUCTS; EXTRACTS; Food Science & Technology